The stake of licence buying companies (LBCs) in the promotion of quality cocoa in Ghana - Goodlet Owusu Ansah; Fredrick Ofori; Lawrencia Pokuah Siaw; John Manu (Cogent Business & Management, 2018)
Ghana as a global bourgeon in cocoa production is attributed as the finest grower of cocoa the world over. Grounded on the cocoa industry's tripartite actors and the fundamental role LBCs play in the domestic supply chain, the study assessed the quality control practices instituted by LBCs in promoting quality cocoa in Ghana. Both qualitative and quantitative methods were espoused in the analyses of responses obtained from a sample size of ninety-five (N = 95) involving 10 District Managers (DMs) and 85 Purchasing Clerks (PCs).The study espoused major quality control practices (QCPs) which is not limited to constant education and training of farmers on proper fermentation, efficient packaging, storage and haulage of goods in transit, proper drying, and removal of placenta and foreign matter. Also, LBCs constantly provide good storage facilities; pallets, tarpaulins, etc., to cocoa farmers, a practice that increases the financial burdens especially the smaller market shareholders. Again, LBCs ensure that their DMs oblige PCs to present high-quality cocoa beans for grading and sealing to the QCC.Findings hypothesise that LBCs are fixated on practices that promote physical quality of cocoa beans to the neglect of biochemical and process quality of the beans. It is therefore proffered that quality promotional efforts be at par to encapsulate the other cocoa quality types in the domestic supply chain.
Keywords: 650